2021
DOI: 10.1186/s12967-021-03083-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene clusters based on OLIG2 and CD276 could distinguish molecular profiling in glioblastoma

Abstract: Background The molecular profiling of glioblastoma (GBM) based on transcriptomic analysis could provide precise treatment and prognosis. However, current subtyping (classic, mesenchymal, neural, proneural) is time-consuming and cost-intensive hindering its clinical application. A simple and efficient method for classification was imperative. Methods In this study, to simplify GBM subtyping more efficiently, we applied a random forest algorithm to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…), this review aimed to conduct a comprehensive, systematic literature review to identify all relevant studies that have significantly reported genes related to overall survival in GBM patients. However, some impact reports on this topic might have been missed due to limitations in the search strategy [ 265 266 ]. In the study future, given the well-established heterogeneity of GBM, the assessment of the prognostic value of specific genes must be conducted with consideration for GBM molecular subtypes, to ensure a comprehensive understanding of their impact, and would pave the way for precision medicine [ 266 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), this review aimed to conduct a comprehensive, systematic literature review to identify all relevant studies that have significantly reported genes related to overall survival in GBM patients. However, some impact reports on this topic might have been missed due to limitations in the search strategy [ 265 266 ]. In the study future, given the well-established heterogeneity of GBM, the assessment of the prognostic value of specific genes must be conducted with consideration for GBM molecular subtypes, to ensure a comprehensive understanding of their impact, and would pave the way for precision medicine [ 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some impact reports on this topic might have been missed due to limitations in the search strategy [265][266]. In the study future, given the well-established heterogeneity of GBM, the assessment of the prognostic value of specific genes must be conducted with consideration for GBM molecular subtypes, to ensure a comprehensive understanding of their impact, and would pave the way for precision medicine [266].…”
Section: Discussionmentioning
confidence: 99%
“…Speci c molecular events in gliomas like EGFR ampli cation, MYB alteration, MAPK pathway alteration, have shown their signi cance according to WHO CNS5 (1). Our previous analysis found GBM with Olig2 or CD276 could share totally different prognosis, and a gene cluster featured with hub genes of Olig2 and CD276 could distinguish molecular subtypes in GBM (4). Interestingly, tumor necrosis factor-α-induced protein 8 (TNFAIP8) was superiorly de ned as one of the independent factors for prognosis in GBM, which favored mesenchymal subtype (4).…”
Section: Introductionmentioning
confidence: 99%